Crystallization, room‐temperature X‐ray diffraction and preliminary analysis of Kaposi's sarcoma herpesvirus LANA bound to DNA. Issue 11 (5th November 2014) - Hellert, Jan; Krausze, Joern; Schulz, Thomas F.; Lührs, Thorsten
<x xml:space="preserve">Abstract</x> The latency‐associated nuclear antigen (LANA) is the latent origin‐binding protein and chromatin anchor of the Kaposi's sarcoma herpesvirus (KSHV/HHV‐8) genome. Its C‐terminal domain (CTD) binds sequence‐specifically to the viral origin of replication, whereas the N‐terminal domain links it to nucleosomes of cellular chromatin for long‐term persistence in dividing host cells. Here, the crystallization and X‐ray data acquisition of a mutant LANA CTD in complex with its wild‐type target DNA LBS1 is described. This report describes the rational protein engineering for successful co‐crystallization with DNA and X‐ray diffraction data collection at room temperature on the high‐brilliance third‐generation synchrotron PETRA III at DESY, Germany.